Influence of Tax Understanding, Service Quality, and Rates on Bandung MSMEs' Tax Compliance with Trust as a Moderator - Rizky Monetary, Rahma (Action Research Literate, 2024)
The summary of the DJP's annual reports from 2017 to 2020 indicates that the achievement percentages are unstable (fluctuating). MSMEs are among the taxpayers contributing to taxation. This study examines and analyzes the influence of tax understanding, service quality, and tax rates on the compliance of MSME actors in Bandung. As a development aspect, this study adds the level of trust as a moderating factor in the relationship between changes in tax rates and the compliance of MSME actors in Bandung. This research model uses multiple regression analysis. The targeted respondents are Online (Digital) MSME Taxpayers in Bandung. The sampling method used in this study is Convenience Sampling, with a total sample of 100 respondents. The analysis tool utilized in this research is the structural least square model (SEM) – partial least square (PLS) using the SmartPLS 3.0 application. The results indicate that understanding tax regulations, the quality of tax services, and changes in tax rates influence taxpayer compliance. Additionally, understanding tax regulations, quality of tax services, and changes in tax rates impact MSME taxpayer compliance with trust in the tax authorities as a moderating variable.